The Role of Women as Breadwinners: A Case Study of Konang Galis Village, Pamekasan - Usmany, Nuri Wahda Salsabila; Al-Humaidy, Mohammad Ali; Efendi, Agik Nur; Rohman, Moh. Mujibur (Adabuna : Jurnal Pemikiran dan Pendidikan, 2025)
The role of women as breadwinners is often considered unusual in Muslim societies, which traditionally associate this role with men. However, in Konang Galis Village, Pamekasan, the phenomenon of women working or even being the main providers for their families has become a common occurrence, unbound by local religious or cultural norms. This study aims to understand the reasons women become breadwinners, their feelings about this role, and the responses from those close to them. Additionally, the research explores their income levels and their hopes for the future of their households. This study employs a qualitative method with a case study approach in Konang Galis Village, Pamekasan. Data were collected through documentation from interviews with two female breadwinners and direct observations in the field. The findings indicate that the reasons for women working vary, ranging from personal desires to economic factors, such as husbands who are unable to work. There is no coercion from any party; in fact, there is support from family and the surrounding environment. The informants earn sufficient income to meet their family needs and express a desire to continue working in the future. This research provides insights into gender dynamics within household economic roles in rural Muslim communities. The results of this study can serve as a reference for gender studies, social policies, and economics, as well as for further research in sociology and Islamic studies.